Post-activation potentiation enhancement induction strategies with different rest intervals on jump performance: a meta-analysis - Zhou, Ying; Zhang, Xiaoqin; Wang, Jian (Frontiers in Physiology, 2026)
ObjectiveThis meta-analysis aimed to systematically evaluate the effects of post-activation potentiation enhancement (PAPE) on jump performance and explore its optimal induction strategies.MethodsRandomized controlled trials (RCTs) investigating the influence of PAPE training on jump performance were retrieved from Web of Science, PubMed, Scopus, and EBSCO. Literature screening was conducted using the Cochrane Risk of Bias Tool. Quality assessment and statistical analyses were performed using RevMan 5.4 software, while sensitivity analysis and funnel plots were employed to evaluate result stability and publication bias.ResultsA total of 22 RCTs involving 468 participants were included. The meta-analysis demonstrated that PAPE significantly improved jump performance [SMD = 1.36, 95% CI (0.89, 1.83), P < 0.0001]. Subgroup analysis indicated that exercise intensity might be a source of heterogeneity across studies.The largest effect sizes with statistical significance were observed in the following subgroups: exercise mode (Back squat) [SMD = 2.85, 95% CI (0.98, 4.73), P = 0.003], gender (Male) [SMD = 1.53, 95% CI (0.92, 2.14), P < 0.0001], outcome extracted (Counter movement jump) [SMD = 1.34, 95% CI (0.86, 1.81), P < 0.0001], exercise intensity (Moderate Intensity) [SMD = 2.46, 95% CI (1.71, 3.22), P < 0.0001], and rest interval (3–7 min) [SMD = 1.47, 95% CI (0.79, 2.14), P < 0.0001].ConclusionPAPE may serve as a potentially effective strategy for enhancing jumping performance under appropriate conditions. In exercises aimed at improving jumping performance, back squats and medium-intensity induction appear to yield the most pronounced benefits. A 3–7 min recovery interval works best, though adjustments should be made based on individual exercise factors.Systematic Review Registrationhttp://inplasy.com, identifier INPLASY202430008.